Enhancing Access to STEM Graphics for Blind and Visually Impaired Students in Nigeria - Adelakun, Sariat; Abdul-Salaam, Aminat; Chukuka, Evangeline; Kehinde, Michael; Shittu, Musibau (Technium Social Sciences Journal, 2025)
Mathematics, Science, Engineering and Technology (STEM) are fundamentals in education with numerous advantages for students. They foster creativity, cultivate critical thinking and, more importantly, open career opportunities. However, for those with visual impairment, these avenues are limited. Blind and Visually Impaired (BVI) students face significant challenges in accessing mathematics and science curricula due to the visual nature of the content. Addressing these challenges would involve rethinking methods of delivering lessons and alternative educational resources. In a cross-sequential study employing observation, unstructured interviews, and critical analysis of documents, this paper assesses the impact of the tactile diagrams component of a STEM Kit on students’ performance in mathematics and basic science and technology (BST). The findings reveal increased participation of BVI students in classroom activities, with notable improvements in their performance in mathematics and basic science and technology. Positive effects were also observed in enhanced participation recorded in other subjects during the study period. These findings underscore the importance of inclusive educational tools in promoting active engagement, academic success, and overall educational equality for blind and visually impaired students in terms of access to STEM, particularly in low- and middle-income countries where such resources are not often readily available.